Biological Control of Tomato Bacterial Wilt, Kimchi Cabbage Soft Rot, and Red Pepper Bacterial Leaf Spot Using Paenibacillus elgii JCK-5075 - Le, Khanh Duy; Kim, Jueun; Yu, Nan Hee; Kim, Bora; Lee, Chul Won; Kim, Jin-Cheol (Frontiers in Plant Science, 2020)
The over and repeated use of chemical bactericides to control plant bacterial diseases has resulted in unwanted effects, such as environmental pollution, residual toxicity, and resistance buildup in bacterial pathogens. Many previous studies have aimed to develop biological control agents to replace chemical bactericides. In this study, the antibacterial efficacy of the fermentation broth of Paenibacillus elgii JCK-5075 and its antibacterial compounds were evaluated against plant pathogenic bacteria, using both in vitro and in vivo bioassays. Pelgipeptins (PGPs) A, B, C, and D that were isolated from P. elgii JCK-5075 displayed broad-spectrum antibacterial activity against various plant pathogenic bacteria. The fermentation broth of P. elgii JCK-5075, at 5-fold dilution, effectively suppressed the development of tomato bacterial wilt, Kimchi cabbage soft rot, and red pepper bacterial leaf spot in pot experiments with control values of 81%, 84%, and 67%, respectively. PGP-A and C, at 200 µg/ml, were also found to markedly reduce the development of Kimchi cabbage bacterial soft rot by 75% and tomato bacterial wilt by 83%, respectively, and their disease control efficacy was comparable to that of oxolinic acid with control values of 81% and 85%, respectively. Additionally, the antibacterial activity of PGP-C was found to be directly correlated with membrane damage mechanisms. These results indicates that P. elgii JCK-5075 producing PGPs could be used as a biocontrol agent for the control of plant bacterial diseases. This is the first report on the in vitro and in vivo antibacterial activity of PGPs against bacterial plant pathogens.